2016
DOI: 10.7863/ultra.15.08050
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Differentiation Between Angiolipomas and Superficial Lipomas

Abstract: Sonography might help differentiate angiolipomas from superficial lipomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…as the differential diagnosis of a large groin mass, includes benign neoplasms of the spermatic cord such as ICLs, fibroma, leiomyoma, hemangioma, cystadenoma, and malignant neoplasms including liposarcoma, leiomyosarcoma, and fibrosarcoma. 7 On ultrasound, a benign fatty mass shows multiple characteristic internal echogenic strands 8 and no or minimal color doppler flow signals. Benign tumors are usually well‐circumscribed, homogeneous and hypoechoic on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…as the differential diagnosis of a large groin mass, includes benign neoplasms of the spermatic cord such as ICLs, fibroma, leiomyoma, hemangioma, cystadenoma, and malignant neoplasms including liposarcoma, leiomyosarcoma, and fibrosarcoma. 7 On ultrasound, a benign fatty mass shows multiple characteristic internal echogenic strands 8 and no or minimal color doppler flow signals. Benign tumors are usually well‐circumscribed, homogeneous and hypoechoic on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that the differences were statistically significant [20]. In addition to these appearances, with respect to the presence of vascularity, tumor length, and tumor width, the difference was detected with statistical significance [20].…”
Section: Subcutaneous Angiolipomamentioning
confidence: 97%
“…They prefer use of a copious amount of gel rather than a standoff pad. Shin et al [20] mentioned that minimal transducer pressure was exerted while maintaining good contact and using a generous amount of gel to avoid underestimation of the blood flow on Doppler study.…”
Section: Dermatological Ultrasound and Acoustic Couplermentioning
confidence: 99%
See 2 more Smart Citations